Science Signaling Podcast for 10 November 2015: Regulation of gene expression by actin dynamics - Muehlich, Susanne; VanHook, Annalisa M. (Science Signaling, 2015)
This Podcast features an interview with Susanne Muehlich, author of a Research Article that appears in the 10 November 2015 issue of Science Signaling, about how actin dynamics can regulate gene expression. The actin cytoskeleton is highly dynamic, with actin filaments polymerizing and depolymerizing to allow cells to move, divide, or maintain their shape. In the polymerized state, actin subunits are referred to as filamentous actin (F-actin), whereas soluble actin monomers are called globular actin (Gactin). Actin dynamics can influence gene expression through changes in the relative abundances of F-actin and G-actin. The transcriptional coactivator MKL1 remains in the cytoplasm when it is bound to G-actin but translocates into the nucleus when it dissociates from G-actin. In the nucleus, MKL1 cooperates with the transcription factor SRF to promote the expression of target genes. Kircher et al. found that MKL1 must also associate with the F-actin-binding protein Filamin A to stimulate target expression.
CRIS-Team Scopus Importer:2024-07-10
Keywords: Actin cytoskeleton; Cytoskeletal dynamics; F-actin; Filamin A; Gactin; Megakaryoblastic leukemia 1; MKL1; Science signaling; Serum response factor; SRF; Transcription factor